Sleep-disordered breathing, circulating exosomes, and insulin sensitivity in adipocytes - Khalyfa, Abdelnaby; Gozal, David; Masa, Juan F; Marin, José Maria; Qiao, Zhuanghong; Corral, Jaime; González, Mónica; Marti, Sergi; Kheirandish-Gozal, Leila; Egea, Carlos; Sánchez-Quiroga, M-Ángeles; de Terreros, Francisco J Gómez; et al. (International Journal of Obesity, 2018)
Background: Sleep-disordered-breathing (SDB), which is characterized by chronic intermittent hypoxia (IH) and sleep fragmentation (SF), is a prevalent condition that promotes metabolic dysfunction, particularly among patients suffering from obstructive hypoventilation syndrome (OHS). Exosomes are generated ubiquitously, are readily present in the circulation, and their cargo may exert substantial functional cellular alterations in both physiological and pathological conditions. However, the effects of plasma exosomes on adipocyte metabolism in patients with OHS or in mice subjected to IH or SF mimicking SDB are unclear. Methods: Exosomes from fasting morning plasma samples from obese adults with polysomnographically-confirmed OSA before and after 3 months of adherent CPAP therapy were assayed. In addition, C57BL/6 mice were randomly assigned to (1) sleep control (SC), (2) sleep fragmentation (SF), and (3) intermittent hypoxia (HI) for 6 weeks, and plasma exosomes were isolated. Equivalent exosome amounts were added to differentiated adipocytes in culture, after which insulin sensitivity was assessed using 0 nM and 5 nM insulin-induced pAKT/AKT expression changes by western blotting. Results: When plasma exosomes were co-cultured and internalized by human naive adipocytes, significant reductions emerged in Akt phosphorylation responses to insulin when compared to exosomes obtained after 24 months of adherent CPAP treatment ( n = 24; p < 0.001), while no such changes occur in untreated patients ( n = 8). In addition, OHS exosomes induced significant increases in adipocyte lipolysis that were attenuated after CPAP, but did not alter pre-adipocyte differentiation. Similarly, exosomes from SF- and IH-exposed mice induced attenuated p-AKT/total AKT responses to exogenous insulin and increased glycerol content in naive murine adipocytes, without altering pre-adipocyte differentiation. Conclusions: Using in vitro adipocyte-based functional reporter assays, alterations in plasma exosomal cargo occur in SDB, and appear to contribute to adipocyte metabolic dysfunction. Further exploration of exosomal miRNA signatures in either human subjects or animal models and their putative organ and cell targets appears warranted.